Integrasi Estetika dalam Pembelajaran di Sekolah Dasar - Asbullah Muslim (MODELING: Jurnal Program Studi PGMI, 2017)
This article is a result of structured research in finding a better learning design that includes aesthetic elements in learning in elementary School in particular and the school in general. Aesthetics is an axiological part of science so that the character enhancement of students can be done in a structured way in learning ptosews. Art as a catalyst of aesthetics is integrated in learning, not only in RPP but in the behavior of students everyday. Art learning is art, dance, music art integrated into the subjects in school curiculum, not just one subject but in all subjects.